Primerjava Bergove lestvice za oceno ravnotežja in testov hoje z indeksom premičnosti de Morton pri bolnikih z mišično-skeletnimi okvarami - Zupanc, Aleksander (Rehabilitacija (Ljubljana), 2020)
Background: Measures that assess mobility do not include all key motor tasks for daily activities. Our aim was to compare the Berg Balance Scale (BBS) and walking tests with the de Morton Mobility Index (DEMMI). Methods: Thirty patients with musculoskeletal impairments, aged from 22 to 84 years (average 54 years) were included in the study. They were assessed at admission to rehabilitation and after four weeks with BBS, ten metre walk test (10MWT), six-minute walk test (6MWT) and DEMMI. We estimated minimal clinically important difference and effect size for all the outcome measures, and assessed floor and ceiling effects. Results: Minimal clinically important difference for BBS was 7 points, for 10MWT it was 0.1 m/s, and for 6MWT it was 40.2 metres. We observed sensitivity to change using all three measures. There were no floor or ceiling effects for BBS and DEMMI at admission and after four weeks. For 10MWT and 6MWT we observed a floor effect at admission, but not after four weeks; there was no ceiling effect at admission or after four weeks. Conclusion: Comparison of Berg balance scale, ten-metre walk test and six-minute walk test with de Morton mobility index showed that all participants improved mobility at least for the minimal clinically important difference only according to de Morton mobility index, which also had higher responsiveness than the other studied measures. We observed a floor effect at admission with both walking tests. Using de Morton mobility index in clinical practise can better assess the mobility level of patients with musculoskeletal impairments.
Keywords: de Morton Mobility Index; DEMMI; effect size; floor and ceiling effects; indeks premičnosti de Morton; MCID; minimal clinically important difference; mobility assessment; Musculoskeletal Diseases; najmanjša klinično pomembna sprememba; ocena premičnosti; rehabilitation; therapeutic use; učinek tal in stropa; velikost učinka; Weights and Measures